Development of teaching materials solubility and solubility product to improve science literacy - H N Fadilah; S Anwar (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to develop teaching materials that can improve science literacy. The method used in this research is Four Steps Teaching Material Development (4S-TMD). 4S-TMD consists of the selection step, the step of structuring, the characterization step and the didactic reduction step. This paper is the first part of the development of teaching materials that includes the step of selection and structuring. At the selection step, an indicator is developed in accordance with the curriculum requirements, explaining the concept, and analyzing the value of skills based on the criteria of science literacy. Furthermore, in the structural step developed concept maps, macro structures and multiple representations that connect between macroscopic, submicroscopic, and symbolic level representations. The results of the selection and structuring steps were evaluated by an expert lecturer in the chemical education department. The results show that the materials developed have been in accordance with the curriculum, in accordance with the students 'cognitive development, scientifically correct, there is the use of interdisciplinary concepts and the appointment of conceptual interrelationships so as to improvee students' science literacy. This first part of the development of teaching materials produces a draft of solubility and solubility product materials to improve science liteteration.